Transnational criminology : trafficking and global criminal markets - Mackenzie, Simon (New horizons in criminology., 2020)
This pioneering study looks across key trafficking crimes to develop a social theory of transnational criminal markets. Looking at how traffickers think of their illegal enterprises as 'just business', it draws broader lessons for the ways forward in understanding criminality in this emerging field.